The Invasive Brazilian Pepper Tree (Schinus terebinthifolius) Is Colonized by a Root Microbiome Enriched With Alphaproteobacteria and Unclassified Spartobacteria - Dawkins, Karim; Esiobu, Nwadiuto (Frontiers in Microbiology, 2018)
Little is known about the rhizosphere microbiome of the Brazilian pepper tree (BP) - a noxious category 1 invasive plant inducing an enormous economic and ecological toll in Florida. Some invasive plants have been shown to drastically change the soil microbiome compared to other native plants. The rhizobacteria community structure of BP, two Florida native plants (Hamelia patens and Bidens alba) and bulk soils were characterized across 6 geographical sites. Although all 19 well-known and 10 poorly described phyla were observed in all plant rhizospheres, BP contained the least total bacterial abundance (OTUs) with a distinct bacteria community structure and clustering patterns differing significantly (pCOA and PERMANOVA) from the natives and bulk soil. BP rhizosphere community contained the highest overall Proteobacteria diversity (Shannon’s diversity 3.25) in spite of a two-fold reduction in richness of the Gammaproteobacteria. Remarkably, the invasive BP rhizosphere was highly enriched with Alphaproteobacteria, dominated by Rhizobiales, including Rhodoplanes and Bradyrhizobiaceae. Also, the relative abundance of Spartobacteria under BP rhizosphere was more than twice that of native plants and bulk soil; featuring unique members of the family Cthoniobacteriaciae (DA101 genus). The trend was different for the family Pedosphaerae in the phylum Verrucomicrobia where the abundance declined under BP (26%) compared to (33-66%) for the H. patens native plant and bulk soil. BP shared the least number of unique phylotypes with bulk soil (146) compared to the other native plants with bulk soil (B.alba -222, H. patens – 520) suggestive of its capacity to overcome biotic resistance. Although there were no specific biomarkers found, taken together, our data suggests that the occurrence of key bacteria groups across multiple taxonomic ranks provide a somewhat consistent profile of the invasive BP rhizo-community. Furthermore, based on the observed prevalence of a bacteria group (Spartobacteria – Cthoniobacteriaciae - DA101); we propose that they have a possible role in BP biology. Our results emphasize the need to further investigate the potential value of ‘unique phylotypes’ in the rhizosphere relative to bulk soil as an ecological tool for monitoring plant-cover / invasion history; or even detecting exotic plants with invasion tendencies.